MicroRNA signatures in endurance athletes: Review of their potential implications - Farwa Baber; Jana Jaklová Dytrtová; Michal Jakl (Rehabilitacja Medyczna)
Introduction: MicroRNAs (miRNAs) are regulators of post-transcriptional gene expression that reflect individual biological adaptations to environmental exposures. Measuring circulating miRNAs offers a way to evaluate biological changes from behavioural interventions, such as exercise and sports, which relate to adaptation, muscle damage and inflammation.Objectives: This review aims to summarize the current knowledge about circulating miRNAs associated with sports, endurance exercise, training and the identification of cardiovascular, as well as myocyte disorders in humans. It is primarily focused on the role of miRNAs in endurance and aerobic training and their regulation in response to cardiac hypertrophy, myocyte damage, fibrosis and inflammation.Material and methods: In this review, the existing literature on miRNA expression is examined in various exercise contexts, identifying key miRNAs involved in the adaptive response to exercise. Research included in the review primarily employed quasi-experimental designs, focusing on pre- and post-exercise miRNA expression changes in elite athletes and healthy individuals.Results: Key miRNAs, such as miR-1, miR-133, miR-21, miR-155, miR-206, miR-208 and miR-146, are highlighted for their significant roles in exercise adaptation. Two key future research directions are identified in the review: investigating the biological pathways linked to different exercise modalities and understanding miRNA expressions in various exercise contexts.Conclusions: Despite varied findings, the review allows to emphasize the need for future research to explore miRNA-gene interactions and the impact of different training types as well as durations, especially comparing athletes to healthy populations. This will help to better understand the relationship between miRNA expression and exercise performance.